Coordinated internodal and paranodal adhesion controls accurate myelination by oligodendrocytes - Elazar, Nimrod; Vainshtein, Anya; Rechav, Katya; Tsoory, Michael; Eshed-Eisenbach, Yael; Peles, Elior (The Journal of cell biology, 2019)
Oligodendrocyte-axon contact is mediated by several cell adhesion molecules (CAMs) that are positioned at distinct sites along the myelin unit, yet their role during myelination remains unclear. Cadm4 and its axonal receptors, Cadm2 and Cadm3, as well as myelin-associated glycoprotein (MAG), are enriched at the internodes below the compact myelin, whereas NF155, which binds the axonal Caspr/contactin complex, is located at the paranodal junction that is formed between the axon and the terminal loops of the myelin sheath. Here we report that Cadm4-, MAG-, and Caspr-mediated adhesion cooperate during myelin membrane ensheathment. Genetic deletion of either Cadm4 and MAG or Cadm4 and Caspr resulted in the formation of multimyelinated axons due to overgrowth of the myelin away from the axon and the forming paranodal junction. Consequently, these mice displayed paranodal loops either above or underneath compact myelin. Our results demonstrate that accurate placement of the myelin sheath by oligodendrocytes requires the coordinated action of internodal and paranodal CAMs.